ASSESSING STUDENTS’ LEARNING IN PROJECT-BASED LEARNING APPROACH - Fitriati (Visipena, 2015)
Students’ passive learning has motivated educators constantly to seek innovative ways to encourage students and improve their learning outcomes. Project-Based Learning (PBL) may be a particularly productive method for transforming practice in ways that support students learning. However, the implementation of PBL is challenging because it requires substantial change to teaching and assessment. The purpose of this paper is to explore new assessment methods that are needed in assessing students’ performance in PBL and how teachers can employ these methods in their practices. The insights provided by Project-Based Learning approach are essential for promoting effective teaching and learning. PBL provides students with an opportunity to engage in the learning process by working collaboratively to solve real-world problem. Moreover, PBL offers the potential to help students become reflective and flexible thinkers who can use knowledge to take an action. This paper emphasizes that the formative approach should be integrated throughout the assessment process, but it should be balanced with observation and tests or tasks in order to provide comprehensive information about student progress and outcomes. Sustained project-based learning is not a simple task for teachers, therefore, teachers need to be involved in professional development programs to get more understanding about what and how assessment might be realized in the project-based approach.